Milk Production and Performance for Some Reproductive Traits of Sheep Breeds and Crosses in the West Bank - Moayed N Ahmed; Jihad M. Abdallah (My University, 2011)
The aim of this study was to investigate milk production and performance for some reproductive traits of Awassiand Assaf breeds and their crosses in the West Bank. The data included 1711 milk records on 1243 ewes and 3682lambing records on 1837 ewes from the Awassi breed (AW), two Awassi-derived-lines (Improved Awassi, IA andAfec-Awassi, AA), Assaf breed (AF), and Awassi x Assaf crosses (XB). The data were from the demonstrationfarms of the Small Ruminant Middle East Regional Program in the West Bank, collected during the years 2003 to2010. The farms covered eight geographic locations (Bethlehem, Dora, Hebron, Jerusalem, Ramallah, Nablus,Qalqilia, and Jenin). For milk traits, the number of ewes (n) and number of records (l) were as follows: n=287,l=435 for AW; n=138, l=224 for IA; n=24, l=40 for AA; n=254, l= 339 for AF, and n=564, l= 758 for XB. Forreproductive traits, these were: n=153, l=431 for IA; n=448, l=778 for AW; n=26, l=56 for AA; n=433, l= 968 forAF, and n=803, l= 1505 for XB. The analysis model for milk traits included: location-breed (LB), Parity (PR), yearseasonof lambing (YS), induction of estrus (TRT: natural or PMSG sponges), number of lambs born per ewelambing (NLB), number of milking tests (NMT), and lactation length (LL). For reproductive traits the modelincluded LB, PR, YS, and TRT. The results showed significant differences in performance among breeds and in theperformance of the same breed in different locations. The least squares means for total milk yield (kg) per ewe over150 days of lactation were: 185.5±8.7 for AA (experimental station of Betqad in Jenin)), 171.4 ±3.7 for IA(experimental station of Betqad), 123.6±4.1 (Jerusalem) to 212.0±7.1 (Hebron) for AW, 184.7±5.2 (Qalqilia) to274.9±8 (Jenin) for AF, and 174.8±3.5 (Dora) to 328.3±7 (Nablus) for XB. The AA line, which carries the Booroolafecundity (FecB) gene, had the highest reproductive performance while AW and IA had the lowest performance.The least squares means of number of lambs born alive per ewe lambing were 1.47±0.06 for AA, 1.15±0.02 for IA,1.11±0.02 (Jerusalem) and 1.19±0.04 (Hebron) for AW, ranged from 1.16±0.05 (Jenin) to 1.31±0.02 (Qalqilia) forAF, and ranged from 1.11±0.03 (Bethlehem) to 1.30±0.06 (Jerusalem) for XB. The least squares means of lambinginterval (in days) were 338±14 for AA, 355±5 for IA, 361±6 (Jerusalem) and 429±14 (Hebron) for AW, rangedfrom 276±11 (Jenin) to 356±16 (Hebron) for AF, and ranged from 269±9 (Jerusalem) to 390±10 (Jerusalem) forXB.

The aim of this study was to investigate milk production and performance for some reproductive traits of Awassiand Assaf breeds and their crosses in the West Bank. The data included 1711 milk records on 1243 ewes and 3682lambing records on 1837 ewes from the Awassi breed (AW), two Awassi-derived-lines (Improved Awassi, IA andAfec-Awassi, AA), Assaf breed (AF), and Awassi x Assaf crosses (XB). The data were from the demonstrationfarms of the Small Ruminant Middle East Regional Program in the West Bank, collected during the years 2003 to2010. The farms covered eight geographic locations (Bethlehem, Dora, Hebron, Jerusalem, Ramallah, Nablus,Qalqilia, and Jenin). For milk traits, the number of ewes (n) and number of records (l) were as follows: n=287,l=435 for AW; n=138, l=224 for IA; n=24, l=40 for AA; n=254, l= 339 for AF, and n=564, l= 758 for XB. Forreproductive traits, these were: n=153, l=431 for IA; n=448, l=778 for AW; n=26, l=56 for AA; n=433, l= 968 forAF, and n=803, l= 1505 for XB. The analysis model for milk traits included: location-breed (LB), Parity (PR), yearseasonof lambing (YS), induction of estrus (TRT: natural or PMSG sponges), number of lambs born per ewelambing (NLB), number of milking tests (NMT), and lactation length (LL). For reproductive traits the modelincluded LB, PR, YS, and TRT. The results showed significant differences in performance among breeds and in theperformance of the same breed in different locations. The least squares means for total milk yield (kg) per ewe over150 days of lactation were: 185.5±8.7 for AA (experimental station of Betqad in Jenin)), 171.4 ±3.7 for IA(experimental station of Betqad), 123.6±4.1 (Jerusalem) to 212.0±7.1 (Hebron) for AW, 184.7±5.2 (Qalqilia) to274.9±8 (Jenin) for AF, and 174.8±3.5 (Dora) to 328.3±7 (Nablus) for XB. The AA line, which carries the Booroolafecundity (FecB) gene, had the highest reproductive performance while AW and IA had the lowest performance.The least squares means of number of lambs born alive per ewe lambing were 1.47±0.06 for AA, 1.15±0.02 for IA,1.11±0.02 (Jerusalem) and 1.19±0.04 (Hebron) for AW, ranged from 1.16±0.05 (Jenin) to 1.31±0.02 (Qalqilia) forAF, and ranged from 1.11±0.03 (Bethlehem) to 1.30±0.06 (Jerusalem) for XB. The least squares means of lambinginterval (in days) were 338±14 for AA, 355±5 for IA, 361±6 (Jerusalem) and 429±14 (Hebron) for AW, rangedfrom 276±11 (Jenin) to 356±16 (Hebron) for AF, and ranged from 269±9 (Jerusalem) to 390±10 (Jerusalem) forXB.
Milk Production and Performance for Some Reproductive Traits of Sheep Breeds and Crosses in the West Bank